ANALISIS PERBEDAAN SEKTOR EKONOMI KREATIF DAN KONTRIBUSINYA TERHADAP PENYERAPAN TENAGA KERJA KOTA SURABAYA (SEBELUM DAN SESUDAH PANDEMI COVID-19) - Ayu Larasati; Ignatia Martha Hendrati; Kiki Asmara (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2021)
This study aims to see the differences in the creative economy sector and their contribution to the absorption of labor in the city of Surabaya (before and after the Covid-19 pandemic). The analytical method used is descriptive method through a quantitative approach where the research is carried out using quantitative data then processed and analyzed so that conclusions can be drawn. By using linear regression analysis tools with dummy variables and ratio analysis of the level of contribution. The results of this study indicate that the creative economy sector and its contribution to the absorption of labor in the city of Surabaya before and after the Covid-19 pandemic do not have a significant effect.